2016
DOI: 10.1590/1414-431x20155034
|View full text |Cite
|
Sign up to set email alerts
|

Genetic aberrations in multiple myeloma characterized by cIg-FISH: a Brazilian context

Abstract: Genetic abnormalities are critical prognostic factors for patients diagnosed with multiple myeloma (MM). This retrospective, multicenter study aimed to contribute with the genetic and clinical characterization of MM patients in a country with continental dimensions such as Brazil. Genetic abnormalities were assessed by cIg-fluorescent in situ hybridization (cIg-FISH) in a series of 152 MM patients (median age 55 years, 58.5% men). Overall, genetic abnormalities were detected in 52.7% (80/152) of patients. A 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
3
2
Order By: Relevance
“…9 In the present study, chromosome abnormalities were identi ed in 56.3% (126/224) of MM patients using FICTION, similar to that reported (53%-69%) in previous studies. 10,11 The detection rate of cytogenetic abnormalities with FICTION was signi cantly higher than direct FISH of 36.6% (52/142) shown in this study. However, FICTION requires an additional laborious cytomorphologic selection process of plasma cells, which are frequently interfered with by background signals overlapping target signals.…”
Section: Discussioncontrasting
confidence: 56%
“…9 In the present study, chromosome abnormalities were identi ed in 56.3% (126/224) of MM patients using FICTION, similar to that reported (53%-69%) in previous studies. 10,11 The detection rate of cytogenetic abnormalities with FICTION was signi cantly higher than direct FISH of 36.6% (52/142) shown in this study. However, FICTION requires an additional laborious cytomorphologic selection process of plasma cells, which are frequently interfered with by background signals overlapping target signals.…”
Section: Discussioncontrasting
confidence: 56%
“…12 In the present study, chromosome abnormalities were identified in 56.3% (126/224) of MM patients using FICTION, similar to that reported (53%-69%) in previous studies. 13,14 The detection rate of cytogenetic abnormalities with FICTION was significantly higher than direct FISH of 36.6% (52/142) shown in this study. However, FICTION requires an additional laborious cytomorphologic selection process of plasma cells, which are frequently interfered with by background signals overlapping target signals.…”
Section: Discussioncontrasting
confidence: 55%
“…With the rapid changes of treatment pattern, the role of prognostic factors for MM has to be reevaluated accordingly. Among MM patients, about 16-24% can be detected with translocation t(11;14)(q13;q32), which ranks with the most common chromosomal translocation (1)(2)(3)(4)(5). Two decades ago, with or without consolidation by ASCT, MM patients with t (11;14) were classified into standard risk, which was supported by some studies (1,3,6,7).…”
Section: Introductionmentioning
confidence: 84%